Unravelling the Imaging Conundrum of Rabies - Ramakrishnan, Banupriya; Sivaramalingam, Geethapriya; Raghavan, Bagyam; Govindaraj, Jayaraj (Indian Journal of Radiology and Imaging, 2022)
Rabies is a major disease burden worldwide, especially in Asia. Approximately, 59,000 human deaths per year occurs in over 150 countries due to rabies, with Africa and Asia contributing 95% of cases. It is a fatal infection of central nervous system (CNS) caused by rabies RNA virus via transmission through bite of an infected animal, aerosols, open wound, or organ transplantation. Magnetic resonance imaging helps in early detection of involvement of CNS and to differentiate rabies encephalitis from other conditions like Guillain-Barre syndrome, acute disseminated encephalomyelitis and other viral encephalitis.
Keywords: rabies encephalitis; atypical imaging; restricted diffusion; hemorrhage